A Failure of Expectation: An Analysis of Entrepreneurial Sense-Making after Business Failure - A Journey through the Narratives of Kenyan Entrepreneurs - Manji, Aleem (2009)
This study seeks to understand how entrepreneurs in small and family businesses make sense of failure. Drawing on the literature as well as interviews conducted with Kenyan Entrepreneurs, a provisional model is proposed as well as numerous mediating factors which highlight that the sense-making process is a continuous one, based on narratives, in which multiple forces are at play.